إدراج وتداول الصكوك في السوك الثانوية: دراسة حالة المملكة العربية السعودية = Listing and trading of Sukuk in the secondary market: a case study of the Kingdom of Saudi Arabia - Alnagar, Ahmed Mohamed Hassan; Othman, Anwar Hasan Abdullah; Zakariyah, Habeebullah (Sakarya University Turkey and the Centre for Research and Development of Human Resources Jordan., 2020)
تلعب الصكوك دورا هاما ضمن استخدامها كأحد أدوات إدارة السيولة بالبنوك الإسلامية، ومع تزايد قيمة إصدارات الصكوك بالمملكة العربية السعودية، يثار تساؤل حول ماهية النشاط بالسوق الثانوي للصكوك بالمملكة؟ وإلى أي مدى يمكن الحكم على نشاط السوق من عدمه؟ وماهية التحديات التي تواجه تطويره والمعالجات المقترحة في هذا الإطار؟ استخدم البحث المنهج الوصفي التحليلي لملاءمته لطبيعة الدراسة وأهدافها. توصل البحث إلى عدم نشاط هذا السوق سواء للصكوك المقيدة بالسوق المحلي "تداول"، أو ما هو مدرج منها بالأسواق الدولية مثل بورصة لندن. بمراجعة أهم التحديات التي تواجه تنشيط السوق الثانوي للصكوك بالمملكة، فقد تم مناقشة ثلاث تحديات أساسية، وهي: ) 1( تحدي الضوابط الشرعية الحاكمة لتداول الصكوك بالسوق الثانوي، وتم التوصل إلى نتيجة مفادها أن الهياكل الشرعية المستخدمة من الأنواع التي فيها إجازة التداول. ) 2( تفضيل غالبية المستثمرين الاحتفاظ بالصكوك حتى تاريخ الإطفاء )الاسترداد(، وهو ما يتماشى مع نفس استراتيجية الاحتفاظ حتى الاستحقاق مثل السندات، ) 3( عدم إتاحة التدا ول لمستثمري التجزئة بالمملكة. ******************************************************************************* Sukuk play an important role within its use as one of the liquidity management tools in Islamic banks, and with the increasing value of Sukuk issuances in the Kingdom of Saudi Arabia, raises questions about what is the activity in the secondary market for sukuk in the Saudi Kingdom? and what extent can market activity be judged or not? What are the challenges facing its development and the proposed treatments in this regard? the research used the descriptive and analytical method to suit its nature and objectives of the study. The research has found that this market is not active, whether for sukuk listed in the local market, "Tadawul", or even what is listed on the international markets such as the London Stock Exchange. By reviewing the most important challenges facing the revitalization of the secondary market for sukuk issued in the Kingdom, three main challenges have been discussed, namely: (1) Challenging Shari'a controls governing the trading of sukuk in the secondary market, the conclusion has been reached that Shari'a structures used are among the types in which they are authorized to trade. (2) Most investors prefer to hold the sukuk until the date of amortization (redemption), which is in line with the financial institution’s strategies like bonds, and then apply the same investment strategy with sukuk, (3) The lack of trading availability for retail investors in the Kingdom.